PENGARUH BUDAYA ORGANISASI DAN MOTIVASI TERHADAP KINERJA PEGAWAI MELALUI KEPUASAN KERJA PADA PT PLN (PERSERO) WILAYAH RIAU DAN KEPULAUAN RIAU KANTOR WILAYAH - Murni, Yemi Tri; ', Marzolina; ', Restu (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This research was conducted at PT PLN (Persero) of Riau and Riau Islands Regional Office where the population is all employees in that office. The samples taken were 65 respondents. The purpose of this study was to determine empirically the influence of organizational culture on employee performance and motivation through job satisfaction at PT PLN (Persero) of Riau and Riau Islands Regional Office. The data obtained were analyzed using path analysis, to test the effect of cultural variables work, motivation to employee performance through job satisfaction. The result showed that organizational culture influence on employee performance and organizational culture influence on employee performance is through the satisfaction of the performance of employees of PT PLN (Persero) of Riau and Riau Islands Regional Office, while the motivation variable does not affect the performance of employees. The researchers suggest the company may need to increase efforts to internalize the organizational culture in the workplace and also more attention to aspects of employee satisfaction in order to support improved performance.Keywords: organizational culture, motivation, employee performance, job satisfaction